Effect Of Variation Of Sugar And Starter Total Quality And Yogurt Acidity Soursop Fruit Skin With Natural Dyes Dragon Fruit - PRASTIWI, Chintia Eka, Dra. Suparti, M.Si (2015)
Yogurt is a fermented milk product with the addition of lactic acid bacteria starter. The bacteria that play a role in the process of fermentation yogurt in general is Lactobacillus bulgaricus and Streptococcus thermophilus. This study aims to determine the quality and total acidity in yoghurt soursop juice with added sugar and plain yogurt starter using organoleptic test and acceptance of society. This type of research is experimental research with the treatment of sugar concentration variations and variations of plain yogurt starter. This study used a completely randomized design (CRD) using the two treatments, the sugar concentration and the concentration of plain yogurt starter, each treatment consisted of three replications. The first treatment is N1 (sugar 7%), N2 (11% sugar), N3 (sugar 15%) as a treatment concentration of sugar. Each treatment was given concentration of plain yogurt starter namely K1 (bacteria 3%), K2 (bacteria 7%) and K3 (11%) at a temperature of 400C. The results showed that the variation of the concentration of sugars and different concentrations of plain yogurt starter affect the organoleptic qualities and the total acidity of yogurt soursop juice and cider dragon fruit skin. Quality yogurt most soursop juice was found in samples of sugar 11% and 7% addition of starter (N2K2) and the sugar samples 15% and 7% addition of starter (N3K2) while the poor results found in samples of sugar 15% and the addition of starter 3% (N3K1). Levels of total acidity of yogurt highest soursop juice found in the treatment of sugar 11% and 11% addition of starter (N2K3) with a concentration of 0.866% total acidity and total acidity levels low of 0.581% in the treatment of sugar 15% and 3% addition of starter (N3K1).